O disjuntivismo fenomênico como defesa do realismo ingênuo - Goncalves, Daniel Borgoni [UNIFESP] (2019)
The thesis deals with the nature of visual perceptual experiences analyzing if phenomenal disjunctivism achieves its goal, that is, to defend naïve realism. Phenomenal disjunctivism is a theory of perception according to which hallucinations and veridical perceptions do not share the same phenomenal character, even though hallucinations seem introspectively indistinguishable from veridical perceptions. Naïve realism is a conception according to which physical objects and their properties determine and constitute veridical perceptual experience. Hence, the phenomenal character of veridical perception would be fulfilled only with physical objects. The terms of art above and rival theories of disjunctivism will be presented and commented to giving us a background of the debate over which this thesis belongs. Following we deal with naïve realism specifically presenting theoretical commitment that phenomenal disjunctivists should adhere. Then we deal with the causal argument from hallucination, the main threat to naïve realism, according to which we could reproduce the experience that occurs in veridical perception without physical objects. Hence, hallucinations would have the same phenomenology of matching veridical perceptions. To defend that veridical perceptions have a sui generis phenomenal character, phenomenal disjunctivists give three kinds of responses that characterizing the following phenomenal disjunctivisms: negative disjunctivism, eliminativist disjunctivism and positive disjunctivism. We will analyze both pro and contra arguments regarding with these three kinds of disjunctivism and we will defend that none achieves its goal. In other words, this thesis defends that negative disjunctivism, eliminativist disjunctivism and positive disjunctivism are not suitable strategies to defend naïve realism.